Morphology of peri-partal placentomes and post-partal foetal membranes in African buffalo (Syncerus caffer) and comparative aspects with cattle (Bos taurus) - Boos, A. (University of Pretoria, 2013)
Dissertation (MSc (Veterinary Science))--University of Pretoria, 2005.